Pemahaman Pendapatan, Pengeluaran dan Penyajian Laporan Keuangan dalam Yayasan Pendidikan Islam dengan Penerapan ISAK 35 - Nurbaeta; Mustakim Muchlis; Puspita H. Anwar (Journal of Economic Education and Entrepreneurship Studies, 2024)
This study aims to determine the form of recording income, expenses and presentation of the foundation's financial statements carried out at the Khadimul Ummah Islamic Education Foundation Kajang Kab. Bulukumba and to find out the foundation's understanding of the application of ISAK 35 standards in disclosing financial statements at the Khadimul Ummah Islamic Education Foundation. This research is a type of qualitative research with a case study approach. The object of research is located at the Khadimul Ummah Islamic Education Foundation, Lembanna Village, Kajang District, Bulukumba Regency. The data used is a type of primary data obtained through the interview data collection method. The data analysis used consists of data reduction stages, presentation of research results, and conclusion drawing. The results showed that the form of recording income and expenses of the Khadimul Ummah Islamic Education Foundation is still very basic and simple, namely only reporting income and expenditure transactions and has not implemented the accounting standards in the preparation of financial statements issued by the current DSAK (Financial Accounting Standards Board), namely ISAK 35. The implication of this research is to provide information related to the presentation of financial statements and as a comprehensive reference for further research, especially on financial statements for non-profit organizations or entities in the future.